2003
DOI: 10.1074/jbc.m305504200
|View full text |Cite
|
Sign up to set email alerts
|

Two Alternative Translation Mechanisms Are Responsible for the Expression of the HCV ARFP/F/Core+1 Coding Open Reading Frame

Abstract: HCV-1 produces a novel protein, known as ARFP, F, or core؉1. This protein is encoded by an open reading frame (ORF) that overlaps the core gene in the ؉1 frame (core؉1 ORF). In vitro this protein is produced by a ribosomal frameshift mechanism. However, similar studies failed to detect the ARFP/F/core؉1 protein in the HCV-1a (H) isolate. To clarify this issue and to elucidate the functions of this protein, we examined the expression of the core؉1 ORF by the HCV-1 and HCV-1a (H) isolates in vivo, in transfected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
1
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 29 publications
6
97
1
4
Order By: Relevance
“…Thus, the initiation of translation of the core11 ORF at internal codons 85/87 resulted in the synthesis of another form of core11 protein shorter than that produced by the 11 frameshift mechanism (F) and known as core11/S (short). However, RRL did not support the synthesis of this form of core11 protein (24). Consistent with our data, Baril and Brakier-Gingras also reported that internal translation initiation, rather than frameshift, was the main mechanism of core11 protein synthesis in cultured human cells and showed that the frameshift mechanism required the presence of the 10 consecutive adenosines within codons 8-11 (21).…”
Section: Alternative Forms Of Core11 Proteins Trans-lated By Frameshisupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, the initiation of translation of the core11 ORF at internal codons 85/87 resulted in the synthesis of another form of core11 protein shorter than that produced by the 11 frameshift mechanism (F) and known as core11/S (short). However, RRL did not support the synthesis of this form of core11 protein (24). Consistent with our data, Baril and Brakier-Gingras also reported that internal translation initiation, rather than frameshift, was the main mechanism of core11 protein synthesis in cultured human cells and showed that the frameshift mechanism required the presence of the 10 consecutive adenosines within codons 8-11 (21).…”
Section: Alternative Forms Of Core11 Proteins Trans-lated By Frameshisupporting
confidence: 67%
“…However, there is no consensus on the nature of the core11 protein, as alternative translation initiation sites and different mechanisms for core11 ORF expression have been described (21)(22)(23)(24) (Fig. 1).…”
Section: Alternative Forms Of Core11 Proteins Trans-lated By Frameshimentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of the minor quasispecies from infected patients with high levels of antibodies against frameshifted proteins would help to address this question. An alternative explanation for the high prevalence of anti-ARFP antibodies would be expression of the core protein +1 ORF by alternative mechanisms such as internal initiation, as described previously (Vassilaki & Mavromara, 2003;Baril & Brakier-Gingras, 2005).…”
Section: Involvement Of Ns5b-dependent Ts In Recodingmentioning
confidence: 99%
“…Additional studies have revealed that this A-rich sequence is also able to induce -1 frameshifting (Choi et al, 2003). More recently, it has been shown that internal initiation near codons 85/87 (Vassilaki & Mavromara, 2003) or at codon 26 (Baril & Brakier-Gingras, 2005) in the core coding sequence may generate products in the +1 reading frame. Previously, we demonstrated another pathway for expression of alternative reading frame products from a genotype 1b sequence (GenBank accession no.…”
Section: Introductionmentioning
confidence: 99%